The project to strengthen Pancasila student profile as an effort to manifest the character of environmental care - Minsih Minsih; Ratnasari Diah Utami; Maryam Nurlaila; Uslan Uslan; Imam Mujahid; Helzi Helzi (Journal of Education and Learning (EduLearn), 2026)
This research aimed to describe the manifestation of the character of environmental care in the project to strengthen Pancasila student profile in the independent curriculum. This study was qualitative research with a phenomenological approach. The subjects of this study were 2 schools, namely elementary school or Sekolah Dasar (SD) Muhammadiyah 1 Ketelan and SD Negeri Karangasem 1. Data collection was conducted through in-depth interviews, observations, and document analysis. Triangulation of sources and methods was conducted to ensure the validity of the data. The data that have been collected were subsequently analyzed in the phase of data reduction, presentation, and conclusion drawing. The results of this study show that the project to strengthen Pancasila student profile in manifesting the character of environmental care has been implemented in these 2 schools. It can be observed in the implementation of sustainable lifestyle projects that are relevant to the Pancasila student profile strengthening project (P5) module, including recycling waste to create business opportunities, reducing plastic waste through the creation of eco-bricks, and processing organic waste into compost, managing waste banks, utilizing the environment as a learning resource and minimizing the use of drinking bottles by using personal tumblers.